PENGARUH PENAMBAHAN IKAN RUCAH PADA PEMBUATAN OPAK SINGKONG TERHADAP SIFAT FISIKOKIMIA - A. Nova Zulfahmi; Ningrum Dwi Hastuti; Irfan Cholid; Yuyun Yuniarti; Assrorudin Assrorudin (Jurnal Teknologi Pangan dan Industri Perkebunan (LIPIDA), 2021)
Opak (cassava crackers) in general contains a lot of carbohydrates. To increase the nutritional value of opak, one of them is by adding trash fish which is quite rich in protein. This study aims to determine the effect of adding trash fish with different concentrations in the manufacture of opak crackers on the physicochemical properties. This study used an experimental method with a RAL experimental design in a laboratory. Sensory testing found that the more concentration of trash fish added, the more favored the panelists with the R3 treatment on average received. Tests for protein and water content produced linear data. The more fish content, the higher the protein content and water content. The highest water and protein content in the R4 treatment was 12.58% and 6.91%, respectively. The highest swelling power (except the control) in treatment R2 was 81.16%, while the least absorption in treatment R4 was 14.11%. These results indicated that the addition of trash fish had a significant effect on the physicochemical properties of opak